Pengembangan Aplikasi Berbasis Mobile untuk Meningkatkan Pengalaman Pelanggan dan Efisiensi Pemasaran dengan Metode ADDIE - Rakhmat, Muhammad Daffa Khairul; Handayani, Irma (Journal of Information System Research (JOSH), 2024)
Sanika, is a Muslim clothing store in Kaligondang Village, Purbalingga Regency. Currently, product marketing uses Whatsapp Group which makes it less effective because potential customers must join the group to get information and place orders. To improve efficiency, this project develops mobile-based applications with REST API technology, which is a link between the admin system and the application system. In the development stages using the ADDIE method is a method used in system development. In this method there are five different steps, which begin with Analysis, Design, Development, Implementation, and Evaluation, so that the stages of work become directed and smooth. The final result of this research is an application that can display a product catalog and can place orders by customers by selecting products directly on the application display, thereby increasing customer experience and efficiency in ordering a product.